2015
DOI: 10.1111/jora.12205
|View full text |Cite
|
Sign up to set email alerts
|

Daily Dynamics of Adolescent Mood and Identity

Abstract: Important linkages between daily mood and identity formation have been theorized, but have not been empirically tested as of yet. This study provided a first examination of these linkages within individuals (N = 392; 55.1% boys; M at T1 = 13.24, SD = 0.44) across 15 series of 5 days distributed over 5 years. Results revealed negative within-time associations of educational and relational commitment with negative mood. Negative mood was positively associated with educational in-depth exploration and educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 77 publications
3
39
2
Order By: Relevance
“…Activity in the vmPFC and rostral/perigenual ACC seems to increase from late childhood through middle adolescence, when it either plateaus or continues to increase. These findings are consistent with empirical evidence and theoretical proposals that adolescence is critical for developing identity .…”
Section: The Development Of Self and Identity In Adolescencesupporting
confidence: 89%
See 1 more Smart Citation
“…Activity in the vmPFC and rostral/perigenual ACC seems to increase from late childhood through middle adolescence, when it either plateaus or continues to increase. These findings are consistent with empirical evidence and theoretical proposals that adolescence is critical for developing identity .…”
Section: The Development Of Self and Identity In Adolescencesupporting
confidence: 89%
“…Adolescence is crucial for many aspects of developing self and identity, including commitments, personal goals, motivations, and psychosocial well‐being . During adolescence, youth seek autonomy, particularly from parents, along with increased commitments to social aspects of identity and greater needs for connection with peers .…”
Section: The Development Of Self and Identity In Adolescencementioning
confidence: 99%
“…Our finding that mood had the strongest prediction for the two identity statuses associated with high identity commitment (foreclosure and achievement) is consistent with previous research (Crocetti et al, ; Hofer et al, ; Schwartz, Beyers, et al, ; Waterman, ), which has found significant correlations between identity commitment and higher mood and wellness states. Because of this connection and the cross‐sectional nature of the completed studies, it is unclear whether (a) a more positive mood helps to stimulate identity commitment, (b) identity commitment leads to more positive moods, (c) identity commitment and positive moods co‐occur, or (d) there is some recursive relationship between positive mood and identity status (Klimstra et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The subprocesses are mood , defined as “the individual's orientation to and beliefs about the individual's future”; communication , defined as “the interpersonal style of being open or defensive to others’ worldviews”; and personal narrative , defined as “the life story that the individual continually creates, largely based on the perceived power and possibility in the individual's life” (E. Eisenberg, personal communication, June 8, 2012). Based on how these aspects fit with McAdams's extensive work on narrative identity (McAdams, ; McAdams & McLean, ) and with the work of others (Klimstra et al, , ; Schwartz, Klimstra, et al, ) examining the bidirectional impact of mood and identity formation, these subprocesses are likely to be involved in how an individual builds a sense of self and also may be important in identity commitment. However, Eisenberg's model has yet to be empirically investigated by anyone in the communication or counseling fields despite more than 100 citations to his article over the last 15 years.…”
Section: Identity Statusmentioning
confidence: 99%
“…Emotion regulation refers to the automatic and volitional processes deployed to modify an individual's affective experiences (13). Improving affective control in adolescents, whose everyday environments can include high levels of negative affect and affective fluctuations (14)(15)(16)(17), may then confer benefits to emotion regulation capacity and mental health.…”
Section: Affective Control Training For Adolescents 4mentioning
confidence: 99%